2006
DOI: 10.1080/09553000600930087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GSM-900 and -1800 signals on the skin of hairless rats. II: 12-week chronic exposures

Abstract: The results of this 12-week chronic study do not demonstrate major histological variations in the skin of hairless rats exposed to RFR used in mobile telephony (GSM-900 or -1800).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In vivo , oxidative stress and fibrosis were induced in rat skin after RFR exposure [60]. Other work by our group did not, however, show any effect on proliferation, epidermis thickness or cell structures in rat skin after a single 2 h exposure to GSM‐900 or GSM‐1800 [60a] or a chronic study up to 12 weeks of exposure [60b].…”
Section: Discussionmentioning
confidence: 98%
“…In vivo , oxidative stress and fibrosis were induced in rat skin after RFR exposure [60]. Other work by our group did not, however, show any effect on proliferation, epidermis thickness or cell structures in rat skin after a single 2 h exposure to GSM‐900 or GSM‐1800 [60a] or a chronic study up to 12 weeks of exposure [60b].…”
Section: Discussionmentioning
confidence: 98%
“…However, we have previously observed that melanocytes are needed to maintain epidermal homoeostasis respective to UV exposure [14,15] Thus, we decided to look at the effect of EMR on epidermal reconstructs containing keratinocytes and melanocytes grown on dead de-epidermized dermis, a physiological model for skin reconstruction. In parallel, to confirm the results of Ennamany et al [9] who used a more physiological dose of exposure (GSM-900, SAR 2 W kg À1 , 6 h) than Sanchez et al [10][11][12] (GSM-900, SAR 2 W kg À1 , 48 h), we also analysed the impact of EMR on reconstructed epidermis without melanocytes. In this study, we measured the variation in the expression of several keratinocyte and melanocyte markers 2, 6 and 24 h after exposure.…”
Section: Introductionmentioning
confidence: 56%
“…Previous studies of EMR on skin were carried out in animal models or reconstructed skin without melanocytes . Using epidermis reconstructed without melanocytes, Sanchez et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations